Studi Usability Testing guna Mendukung Akses Informasi yang Lebih Mudah pada Prototype Sistem SDM PT. Iframe Solusi Multimedia, Sleman, Yogyakarta - Pratama, Bayu Surya; Sujarwadi, Agus (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2023)
Human resources (HR) is the key to business success, so HR must be supported by a strong information system. This is done to measure system availability to find out a low level of availability. so that the quality used can be measured in accordance with the requirements. Therefore, usability testing is used. This test will use instrument testing using the System Usability Scale (SUS) method. This usability test determines how easy the system is to use. It is hoped that the system to be built will facilitate access to human resource services. Utilizing the SUS calculation, this test involves six participants with a rating scale of 1-5. The results show that the system is considered good and feasible to use with a score of SUS 70.